DEVELOPMENT AND CHARACTERIZATION OF BIOCOMPATIBLE POLYHYDROXY BUTYRATE IMPREGNATED WITH HERBAL PLANTS AGAINST WOUND HEALING ACTIVITY ON IN VIVO ANIMAL MODEL - R, RAM NARENDRAN; BEGUM SF, MALEEKA; S, RUBAVATHI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current study is to evaluate the antimicrobial, antioxidant, anti-inflammatory, and in vitro cytotoxicity activities of polyhydroxybutyrate (PHB) and to develop the herbal impregnated PHB cast film for wound healing activities using Albino Wistar rat model. Methods: PHB produced by Azotobacter chroococcum A3 strain was synthesized and characterized (previous study). The PHB was subjected to various biocompatibility studies such as antimicrobial, antioxidant, and anti-inflammatory studies. The PHB was also subjected to cytotoxicity study by (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. PHB films were made using different combinations of plant and algal blends (herbal blends). The herbal blends of PHB films were evaluated for in vivo wound healing activity using Albino Wistar rats. Results: The turmeric impregnated PHB showed the highest result for antimicrobial with 27.25±0.23 mm against skin pathogens and antioxidant activity with the highest percentage of inhibition of 76%. The result predicts that PHB will not let to any toxic substances rather it acts as a chemoprotective agent followed by the inhibitory concentration value was found to be 1.56 μg/ml for 100 μg. The in vivo study showed better wound healing activity for PHB blended with 2% turmeric leaf and rhizome cast film. Whereas the wound healing activity of control and crude PHB was 90.4±0.4 and 91.3±0.56 respectively. Conclusion: The results from the present study showed that PHB can act as a good candidate for drug carrier and it is biocompatible in living cells.